A Defect-Correction Mixed Finite Element Method for Stationary Conduction-Convection Problems. (9th January 2011) - Si, Zhiyong; He, Yinnian
Abstract : A defect-correction mixed finite element method (MFEM) for solving the stationary conduction-convection problems in two-dimension is given. In this method, we solve the nonlinear equations with an added artificial viscosity term on a grid and correct this solution on the same grid using a linearized defect-correction technique. The stability is given and the error analysis inL 2 andH 1 -norm ofu, T and theL 2 -norm ofp are derived. The theory analysis shows that our method is stable and has a good precision. Some numerical results are also given, which show that the defect-correction MFEM is highly efficient for the stationary conduction-convection problems.